THE ROLE OF WORK IN HUMAN AESTHETIC ACTIVITY (American Journal of Research in Humanities and Social Sciences, 2023)
The main focus of the article is on the human factor, on the historical diversity of the ability to work, as well as on the qualitative processes inherent in the labor process, and on the aesthetic pleasure of a person in the pursuit of creative and high goals.